Contribution Behavior in Virtual Communities: Cognitive, Emotional, and Social Influences1 - Tsai, Hsien-Tung; Bagozzi, Richard P. (MIS Quarterly, 2014)
The long-term viability of virtual communities depends critically on contribution behavior by their members. We deepen and extend prior research by conceptualizing contributions to virtual communities in terms of small friendship group–referent intentional actions. Specifically, we investigate cognitive, emotional, and social determinants of shared we-intentions and their consequences for member contribution behavior to the small friendship group to which they belong within a larger community. Using multiple measurement sources and a longitudinal quasi-experimental design, we show that group norms and social identity, as well as attitudes and anticipated emotions, contribute to the development of behavioral desires, which in turn influence we-intentions. In addition, subjective norms are less effective than either group norms or social identity in encouraging contribution behavior. Finally, members’ experience levels positively moderate the relationship between we-intentions and contribution behaviors, and differences between collectivistic versus individualistic orientations moderate the effects of social identity and anticipated emotions on the desire to contribute to one’s friendship group in the virtual community. Tests for methods biases were conducted, as well as rival hypotheses. These findings have significant research and managerial implications.